Aqueous‐Phase Hydrodeoxygenation of Biomass Sugar Alcohol into Renewable Alkanes over a Carbon‐Supported Ruthenium with Phosphoric Acid Catalytic System. Issue 5 (14th February 2017) - Weng, Yujing; Wang, Tiejun; Qiu, Songbai; Wang, Chenguang; Ma, Longlong; Zhang, Qi; Chen, Lungang; Li, Yuping; Sun, Fei; Zhang, Qian
Abstract: Recently, we demonstrated the catalytic conversion of biomass hydrolysate and real biomass into renewable alkanes over a Ru/C catalyst with aqueous phosphoric acid (Ru/C+H3 PO4 ) and we obtained a high yield of C5 /C6 alkanes. In this study, the mechanism of sorbitol hydrodeoxygenation (HDO) into alkanes over the Ru/C+H3 PO4 catalytic system was investigated by using a trickle‐bed reactor. A high HDO performance was detected with a large amount of long‐chain alkanes in the products. Subsequently, pre‐ and postcharacterization studies (N2 adsorption, XRD, X‐ray photoelectron spectroscopy, TEM, NH3 temperature‐programmed desorption, H2 temperature‐programmed reduction, FTIR spectroscopy) were performed on the relevant catalysts to study the change of the catalytic active sites. Moreover, mineral acid experiments were performed to study the influence of phosphoric acid on the HDO performance. Abstract : Renewable alkanes : The mechanism of sorbitol hydrodeoxygenation (HDO) into alkanes over the Ru/C+H3 PO4 catalytic system is investigated by using a trickle‐bed reactor. A high HDO performance is detected with a large amount of long‐chain alkanes in the products.